Comparative Effects of Shadow Drill and Slalom Dribble Training on Dribbling Skills Among Football Extracurricular Students at SMA Negeri 2 Tanjung Morawa - Simanullang, Hottua Isra Fernandes; Munawar, Ahmad Al (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This empirical study aims to analyze the comparative effects of Shadow Drill and Slalom Dribble training methods on the improvement of dribbling skills among football extracurricular students at SMA Negeri 2 Tanjung Morawa, Deli Serdang Regency. Employing an experimental design with a pre-test and post-test two-group format, the research involved 18 student-athletes selected through total sampling. Participants were divided equally into two groups: Group A received Shadow Drill training, while Group B underwent Slalom Dribble training, each for six weeks. The dribbling performance was measured using a standardized soccer dribbling test, and data were analyzed using a t-test for significance. The results revealed that both training methods significantly enhanced students’ dribbling performance (p < 0.05). However, the Shadow Drill method demonstrated a greater positive effect compared to the Slalom Dribble method. This finding suggests that the reactive and adaptive nature of Shadow Drill exercises enhances motor coordination, focus, and ball control, contributing to superior dribbling skills development. The study reinforces the pedagogical importance of varied and interactive training drills in optimizing technical performance in youth football programs.